Novel polyphosphazene-hydroxyapatite composites as biomaterials. - Laurencin, C.T.
Evaluating a polymer-ceramic biomaterial as a candidate for bone tissue engineering. The objective of the present work was to develop novel composites of biodegradable polyphosphazenes and HA as candidate materials for bone tissue engineering. The mechanical and degradation properties of novel PPHOS/HA composites were compared to PLAGA/HA composites as PLAGA being the most extensively investigated polymer for bone tissue engineering application.
Keywords: Biodegradable polyphosphazenes; Biomaterials; Bone tissue engineering; Degradation; Mechanical strength; Polymer; Polyphosphazene-hydroxyapatite composites